Lactate Dehydrogenase C Produces S-2-Hydroxyglutarate in Mouse Testis - Teng, Xin (ACS Chem Biol, 2016)
Metabolomics is a valuable tool for studying tissue- and organism-specific metabolism. In normal mouse testis, we found 70 μM S-2-hydroxyglutarate (2HG), more than 10-fold greater than in other tissues. S-2HG is a competitive inhibitor of α-ketoglutarate-dependent demethylation enzymes and can alter histone or DNA methylation. To identify the source of testis S-2HG, we fractionated testis extracts and identified the fractions that actively produced S-2HG. Through a combination of ion exchange and size exclusion chromatography, we enriched a single active protein, the lactate dehydrogenase isozyme LDHC, which is primarily expressed in testis. At neutral pH, recombinant mouse LDHC rapidly converted both pyruvate into lactate and α-ketoglutarate into S-2HG, whereas recombinant human LDHC only produced lactate. Rapid S-2HG production by LDHC depends on amino acids 100–102 being Met-Val-Ser, a sequence that occurs only in the rodent protein. Other mammalian LDH can also produce some S-2HG, but at acidic pH. Thus, polymorphisms in the Ldhc gene control testis levels of S-2HG, and thereby epigenetics, across mammals.